The research of new markers of inflammation in patients with coronary artery disease and diabetes mellitus type 2 - Хвисюк, Мария Алексеевна (ScienceRise: Medical Science, 2016)
The prevalence of coronary disease among adult population of Ukraine is 9 %. This parameter increases with age and is 5–7 % at the age of 45–64 years and 10–14 % at the age of 65–84 years. In 2011 52 mln of European people at the age of 20–79 years suffered from diabetes mellitus and, according to prognostications of Diabetes International Federation, this rate will increase till 2030 up to 64 mln. People with coronary disease and concomitant diabetes mellitus are more inclined to the proinflammatory changes and thrombus creation comparing with ones, who do not suffer from diabetes mellitus. At present it is known, that inflammation plays the important role in atherogenesis, including initiation, development of the vascular wall injury, atheroma instability and appearance of thrombotic complications. Atherosclerosis is considered as the long-term, torpid chronic inflammation in vascular intima. Such conception explains the connection between inflammation mediators and risk factors of atherosclerosis development. The changes of basal level of the new inflammation markers (Galectin-3, P-selectin) in patients with CD in combination with diabetes mellitus type 2 remains unstudied for today; The aim of research is the study of the role of new pathogenetic markers of inflammation in patients with coronary disease and concomitant diabetes mellitus, elaboration of the methods of their correction, elaboration of the new approaches to therapy using the received results